Evaluation Of Relationship Between Endoscopic Activity Index and Inflammatory Indicators Such as Fecal Calprotectin, C-Reactive Protein to Albumin Ratio, Neutrophil to Lymphocyte Ratio, Platelet to Lymphocyte Ratio in Ulcerative Colitis Patients: - - Taghvaei , Tarang; Hashemi, Seyyed Abbas; Maleki , Iradj; Ebrahimi , Mahboobe; Kazemi, Arash; Ebrahimi Shahabi , Reyhane; Yazdani Charati , Jamshid (Journal of Medical Biochemistry, 2025)
Objective: This study aimed to evaluate the association between low-cost inflammatory biomarkers and disease severity in ulcerative colitis (UC), with a focus on predicting acute severe ulcerative colitis (ASUC) or disease activity (Mayo score >1). Methods: An analytical cross-sectional study was conducted among 131 UC patients from Imam Khomeini Hospital, Iran (2022–2024). Demographic, clinical, and laboratory data—including neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), CRP-to-albumin ratio (CAR), and fecal calprotectin—were analyzed. Disease severity was assessed via the Mayo endoscopic score. Statistical analyses included chi-square tests, ANOVA, logistic regression (adjusted for age, sex, BMI). Results: Participants (mean age 45.8 ± 15.9 years) had elevated inflammatory markers (CRP: 32.6 ± 39.1 mg/L; ESR: 44.0 ± 21.5 mm/hr). Defecation frequency ≥6/day was strongly associated with ASUC (χ²(2) = 101.10, p < .001). PLR’s third quartile (14–20) independently predicted ASUC after adjustment (OR = 2.57, p = .034). Monocyte percentage differed significantly between ASUC and non-ASUC groups (F(1,30) = 6.52, p = .016). NLR and CAR showed no significant associations. There was a significant difference in PLR between the active (median (IQR): 133.87 (96.15- 190.63)) and non-active groups (median (IQR) : 129.61(102.15-209.98), p=0.029; while non-significant AUC achieved for detection of active UC. Conclusion: PLR may partially serve as practical biomarkers for ASUC risk stratification or active UC, while monocyte levels could indicate disease severity. These findings support the use of routine blood indices in UC management.